A Study on the Sports Injuries in Wushu Teaching at Beichen Children’s Art School in Hohhot - Xiao, Jianwei (Pacific International Journal, 2023)
Wushu, also known as Chinese martial arts, is a traditional sport and cultural treasure of China that has a history of thousands of years. In China, Wushu is widely practiced and has been integrated into the national physical education curriculum, with Wushu being taught in schools and training centers across the country. This study adopts research methods such as survey, literature review, and statistics to investigate and analyze the injuries that occur in Wushu teaching at Beichen Children’s Art School in Hohhot,China, with the aim of exploring the causes and preventive measures of these injuries and reducing their occurrence in Wushu teaching. The integrated approach of combining internal and external training, as well as the unity of form and spirit, is a major feature of Wushu practice. "Internal" refers to the mental and breath-related activities of the heart, mind, intention, and qi. "External" refers to the external physical activities of the hands, eyes, body, and steps. Many martial arts styles and schools emphasize the integrated approach of internal and external training and the unity of form and spirit. Wushu practice not only has a high exercise value but also has rich content and diverse forms. Different boxing and equipment have different action results, technical requirements, styles, and exercise volumes. It can be carried out without limitation by age, gender, time, season, venue, or equipment. People can choose appropriate projects for exercise according to their needs and conditions, which provides convenient conditions for carrying out mass sports activities. Therefore, Wushu practice has a wide range of adaptability.